Models of neuroinflammation for the assessment of kappa-opioid receptor ligands - K. Yu. Kalitin; A. A. Spasov; O. Yu. Mukha (Фармация и фармакология (Пятигорск))
The development of new drugs to combat neuroinflammation is highly relevant as it opens up possibilities for the treatment of a wide range of diseases, including Alzheimer’s disease, Parkinson’s disease, epilepsy, schizophrenia, depression, and others. Kappa-opioid agonists represent a promising class of compounds with а high potential to be used in the treatment of neurological conditions accompanied by neuroinflammation.The aim of the study was to provide a summary of the current strategies employed to evaluate the neurotropic anti-inflammatory effects of kappa-opioid ligands in laboratory animals with induced neuroinflammation.Materials and methods. The databases, such as Google Scholar, PubMed, ScienceDirect, Scopus, e-Library were used as search tools. The search comprised the following keywords and phrases in Russian and English: kappa opioids + neuroinflammation; kappa opioid receptors + neuroinflammation; neuroinflammation models; neuroinflammation models in rats, neuroinflammation models in mice. 148 relevant articles were found, 122 were included in this review.Results. Various experimental models of neuroinflammation, including chemically-induced and bacterial endotoxin-induced neuroinflammation, as well as traumatic and genetic models in mice and rats were evaluated. In addition, the strengths and limitations of each model were critically assessed to identify the most appropriate and reliable approach for investigating the relationship between neuroinflammation and signaling pathways associated with kappa-opioid receptors.Conclusion. The neurotropic anti-inflammatory activity of kappa-opioid ligands have been comprehensively described. The review discusses both experimental models where the effects of kappa-opioid agonists have been investigated, as well as the models where the anti-inflammatory properties of kappa-opioid agonists have not been studied yet.